Spatial Diversification of Municipal Expenditure for Residual Charges for Inhabitants of Collective Households in Poland. Present Situation and Prognosis - Bobrowska, Agnieszka Monika; Maciejasz-Świątkiewicz, Marta (Acta Universitatis Lodziensis. Folia Oeconomica, 2018)
Communes as the smallest units of local government in Poland are responsible for social assistance. The growing number of older people can affect the level of care expenses, including these that are spent for care in social welfare houses (SWH). The expenses of municipalities related to the residence of their inhabitants in SWH are increasing systematically, and they are becoming a substantial problem especially for communes at lower socio‑economic development level. The aim of this paper is to identify those voivodeships in which communes are and will be mostly affected in the near future by residual charges for inhabitants of SWH and to check whether this is related to the demographic situation. Statistical data analyzed in this paper were taken from public sources: Ministry of Family, Labour and Social Policy reports, and Central Statistical Office. The current situation of voivodeships in the area of population aging and the expenditures on residual charges for inhabitants of SWH were described. There was diagnosed a diversification of voivodships due to the level of expenditures connected with residual charges for inhabitants of SWH and the lack of diversification due to the participation of the elderly in the population. Basing on linear trend models there was also prepared a forecast of expenditures of communes in the perspective up to 2020. It was shown that the communes located in the warmińsko‑mazurskie voivodship would have to face the greatest level of expenditures (per capita). The expenditures per capita in this voivodeship will be more than two times of the mazowieckie voivodship’s expenditures.